Antibacterial Activity of Stenotrophomonas maltophilia Endolysin P28 against both Gram-positive and Gram-negative Bacteria - Dong, Hongling; Zhu, Chaoyang; Chen, Jingyi; Ye, Xing; Huang, Yu-Ping (Frontiers in Microbiology, 2015)
Maltocin P28 is a phage-tail like bacteriocin produced by Stenotrophomonas maltophilia P28. The ORF8 of maltocin P28 gene cluster is predicted to encode an endolysin and we name it endolysin P28. Sequence analysis revealed that it contains the lysozyme_like superfamily conserved domain. Endolysin P28 has the four consensus motifs as that of Escherichia coli phage lambda gpR. In this study, endolysin P28 was expressed in E. coli BL21 (DE3) and purified with a C-terminal oligo-histidine tag. The antibacterial activity of endolysin P28 increased as the temperature rose from 25 to 45°C. Thermostability assays showed that endolysin P28 was stable up to 50°C, while its residual activity was reduced by 55% after treatment at 70°C for 30 min. Acidity and high salinity could enhance its antibacterial activity. Endolysin P28 exhibited a broad antibacterial activity against 14 out of 16 tested Gram-positive and Gram-negative bacteria besides S. maltophilia. Moreover, it could effectively lyse intact Gram-negative bacteria in the absence of ethylenediaminetetraacetic acid as an outer membrane permeabilizer. Therefore, the characteristics of endolysin P28 make it a potential therapeutic agent against multi-drug-resistant pathogens.